Environmental Health and Traditional Fuel Use in Guatemala - Ahmed, Kulsum; Awe, Yewande; Barnes, Douglas F.; Cropper, Maureen L.; Kojima, Masami (2012)
Recognition of the problem of indoor air pollution (IAP) and its deleterious effects of health is growing worldwide as efforts increase to understand and articulate the complex health-air pollution linkages. Recent WHO estimates indicate that indoor smoke for solid fuels causes 1.6 million deaths annually and accounts for 2.7 percent of the global burden of disease. In Guatemala, adverse health impacts of IAP disproportionately affect children in poor, rural households of which 97 percent use fuelwood as the dominant cooking fuel. Based on data from two recent household surveys and the results of worldwide IAP health studies, this book examines the relationship between fuel use and health in Guatemala. The main purpose of the book is to draw attention to a major problem by highlighting the effects of IAP on the health of children in rural households in Guatemala and to identify appropriate options to mitigate those effects.